The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1124/jpet.107.121491
|View full text |Cite
|
Sign up to set email alerts
|

Species Difference in the Inhibitory Effect of Nonsteroidal Anti-Inflammatory Drugs on the Uptake of Methotrexate by Human Kidney Slices

Abstract: Simultaneous use of nonsteroidal anti-inflammatory drugs (NSAIDs), probenecid, and other drugs has been reported to delay the plasma elimination of methotrexate in patients. Previously, we have reported that inhibition of the uptake process cannot explain such drug-drug interactions using rats. The present study quantitatively evaluated the possible role of the transporters in such drug-drug interactions using human kidney slices and membrane vesicles expressing human ATP-binding cassette (ABC) transporters. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
113
0
6

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(126 citation statements)
references
References 33 publications
7
113
0
6
Order By: Relevance
“…As a result, expression of a MDR phenotype in human malignant cells may not always be sensitive to potentiation of drug cytotoxicity by NSAIDs (Roller et al, 1999). The present results also confirmed other studies that show NSAIDs' effects are cell and efflux transporter specific (Nozaki et al, 2007).…”
Section: The Influence Of Indomethacin On Abcg2 Expression and Functionsupporting
confidence: 88%
“…As a result, expression of a MDR phenotype in human malignant cells may not always be sensitive to potentiation of drug cytotoxicity by NSAIDs (Roller et al, 1999). The present results also confirmed other studies that show NSAIDs' effects are cell and efflux transporter specific (Nozaki et al, 2007).…”
Section: The Influence Of Indomethacin On Abcg2 Expression and Functionsupporting
confidence: 88%
“…A previous retrospective study demonstrated that the coadministration of NSAIDs was not a risk factor for the development of hematologic toxicity by pemetrexed (Sakata et al, 2013); however, NSAIDs are known as substrates and/or inhibitors of hOAT3 (Uwai et al, 2004;Nozaki et al, 2007). A clinical study has reported that a 20% increase in the area under the plasma concentration curve of pemetrexed was observed when 400 mg of ibuprofen was administered orally every 6 hours .…”
Section: Discussionmentioning
confidence: 99%
“…When MTX is used at high-dose regimens for cancer treatment, interactions with NSAIDs can result in severe toxicity, with sometimes fatal outcome (Thyss et al, 1986). In a recent study, using human kidney slides, it was demonstrated that diclofenac and its acyl-glucuronide can inhibit the luminal urinary efflux of MTX via the ATP-binding cassette (ABC) multidrug transporters Mrp4 and Mrp2, respectively (Nozaki et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…When MTX is used at high-dose regimens for cancer treatment, interactions with NSAIDs can result in severe toxicity, with sometimes fatal outcome (Thyss et al, 1986). In a recent study, using human kidney slides, it was demonstrated that diclofenac and its acyl-glucuronide can inhibit the luminal urinary efflux of MTX via the ATP-binding cassette (ABC) multidrug transporters Mrp4 and Mrp2, respectively (Nozaki et al, 2007).Because it is recognized more and more that many interactions of drugs occur at the level of drug-transporting proteins, we investigated whether diclofenac is a substrate of one of the apical ABC transporters, using MDCK-II cells transfected with human P-gp, MRP2, BCRP, or murine Bcrp1 cDNA. We further used the MDCK-II cells transduced with human and mouse MRP2/Mrp2 to examine whether diclofenac could modulate MRP2-mediated transport of taxane anticancer drugs.…”
mentioning
confidence: 99%